A STUDY OF THE COGNITIVE PROCESSING MODELS USED IN THE APPRAISAL SYSTEM: THE MALAYSIAN PUBLIC SERVICE - Rusli Ahmad ,; David P. Spicer , (Asian Academy of Management Journal, 2002)
The purpose of the paper is to present the results of semi-structured interviews undertaken with expert raters (School Principals) within the Malaysian Education System. These interviews have been conducted using a cognitive mapping protocol. The resultant causal cognitive maps are explored for what they have to tell us about the Cognitive Processing Models (CPM) applied in appraisal decision-making. From the research findings, it is clear that raters recognized the CPM steps in their performance appraisal (PA) practice. The study also identifies the differences between individual expert raters in terms of concepts and complexity in the decision making process. Finally, the study discusses the implications of the research for the CPM and appraisal decision-making process.